Peripheral Third Cranial Nerve Enhancement in Multiple Sclerosis - Bhatti, M. Tariq; Schmalfuss, Ilona M.; Williams, Lorna S.; Quisling, Ronald G. (American Journal of Neuroradiology, 2003)
Summary: Cranial nerve III dysfunction in multiple sclerosis (MS) is uncommon. Seven cases of isolated cranial nerve III paresis associated with MS have been reported in the English-language literature. MR imaging was obtained in five cases demonstrating lesions within the midbrain. We present the detailed clinical and MR imaging findings of a young woman with MS and an isolated, painful pupil involving complete left cranial nerve III palsy. Initial MR imaging showed isolated enhancement of the cisternal portion of the cranial nerve III, suggesting that peripheral nervous system involvement may develop as part of the disease process in some patients with MS.